Implementasi dan Peningkatan Program Moderasi Beragama Berbasis Digital di Pondok Pesantren Ittihadul Asna Kota Salatiga Melalui Program Pemberdayaan Masyarakat - Zaim, Muchammad; Saifudin (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2025)
This research aims to analyze the effectiveness of the "Digital-Based Religious Moderation" program implemented at Islamic Boarding School Ittihadul Asna Salatiga. Using a qualitative approach, data were collected through focus group discussions (FGD), observations, in-depth interviews, and documentation. The results indicate that this program significantly enhances children's understanding of the values of religious moderation and facilitates the use of technology in the learning process. Children exhibit increased attitudes of tolerance and mutual respect, as well as a high interest in the material presented through digital media. Support from the Islamic Boarding School management and village government plays a crucial role in the success of this program. These findings suggest the importance of synergy between educational institutions and the community in creating an environment that supports character education amid social diversity.